2022
DOI: 10.1017/s0014479722000370
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil aggregate-associated carbon sequestration capacity after 14 years of conservation tillage

Abstract: Summary The North China Plain is an important summer maize/winter wheat rotation area. However, over the years, continued intensive tillage has destroyed the soil aggregate accelerating the mineralization and decomposition of soil organic carbon (SOC), which plays an important role in soil quality, as increased organic carbon storage improves soil fertility and crop yields. Thus, the objective of this study was to explore the comprehensive impact of tillage methods on soil aggregates, aggregate-associated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Soil aggregates are the key determinants of nutrient exchange in soil and the basic constituent unit of soil structure [1,2]. The stability of soil aggregates and soil organic matter are important characteristics influencing soil quality, environmental sustainability, and crop yield in agricultural systems [3,4]. At the same time, soil aggregate stability is a viable and effective factor in understanding the complex interactions between soil physicochemical properties and soil structure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Soil aggregates are the key determinants of nutrient exchange in soil and the basic constituent unit of soil structure [1,2]. The stability of soil aggregates and soil organic matter are important characteristics influencing soil quality, environmental sustainability, and crop yield in agricultural systems [3,4]. At the same time, soil aggregate stability is a viable and effective factor in understanding the complex interactions between soil physicochemical properties and soil structure [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve these problems, we studied the effects of sustainable conservation tillage on soil carbon and nitrogen storage and CPMI in the wheat field on a Loess Plateau, this study will provide theoretical basis and basic data for understanding the dynamic changes of farmland soil organic carbon and nitrogen storage and the carbon and nitrogen sequestration potential of conservation tillage measures. For this reason, we put forward some assumptions: (1) The implementation of sustainable conservation tillage may positively affect the content of carbon and nitrogen components in the soil by reducing the disturbance to the soil and improving the soil texture (2) Sustainable conservation tillage may enhance soil compactness, increase soil organic carbon and TN content, and then increase soil carbon and nitrogen storages (Chen et al, 2022); (3) Sustainable conservation tillage may significantly affect soil carbon pool, compared with traditional tillage, it will improve CPMI and has good carbon and nitrogen sequestration potential (Yadav et al, 2021). We believe that this study will contribute to the sustainable development of the regional farmland ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies concluded that the adoption of no-tillage promotes aggregate formation in surface soils and effectively increases the number of MSA [11] and WSA compared with conventional tillage [12]. Other studies suggested that the application of subsoiling can increase the WSA content in the 0-40 cm soil layer compared with conventional tillage [13] and increase the >0.25 mm WSA in the 0-5 cm soil layer compared with no-tillage [14]. Differences in the results may be related to site-specific conditions such as climate, soil texture, sampling time, cropping system, and tillage intensity.…”
Section: Introductionmentioning
confidence: 99%